Impacts of an Early Childhood Mathematics and Science Intervention on Teaching Practices and Child Outcomes. Issue 2 (2nd April 2020) - Whittaker, Jessica V.; Kinzie, Mable B.; Vitiello, Virginia; DeCoster, Jamie; Mulcahy, Christina; Barton, Emily A.
Abstract: This randomized controlled trial examined effects of the MyTeachingPartner-Math/Science intervention on the quality and quantity of teachers' mathematics and science instruction, and children's mathematics and science outcomes in 140 pre-kindergarten classrooms. Teachers participated in the intervention for two years with consecutive cohorts of children. Results from Year 1 are considered experimental, however due to high levels of attrition, results from Year 2 are considered quasi-experimental. Across both years, intervention teachers exhibited higher quality and quantity of instruction. In Year 1, there were no significant effects of the intervention on children's outcomes. In Year 2, children in intervention classrooms made greater gains in teachers' ratings of mathematics and science skills and performed better on a spring assessment of science skills. These results have implications for designing and evaluating professional development aimed at supporting children's mathematics and science knowledge and skills.